Double Movement Theory in Fazlur Rahman's Thought: Social and Religious Applications and Their Impact on Modern Understanding - Dedisyah Putra; Martua Nasution; Nuriza Acela (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
Fazlur Rahman, a leading Islamic thinker of the 20th century, proposed the concept of double movement as an important structure for analyzing the relationship between tradition and modernity in Islamic thought. The term “double movement” reflects Rahman's theory that the evolution of Islamic society included two fundamental movements. This type of research is qualitative research, using library research methods or also called literature review research with a character study approach. Fazlur Rahman's concept of double movement encapsulates the belief that the understanding and interpretation of Islamic teachings must occur in two areas: The First implies a commitment to the written sources and essential doctrines of Islam, while the Second movement represents the rapid adaptation of these teachings into everyday life. day. This theoretical picture stems from a critique of static interpretations of religious texts, which are believed to fall into dogmatism and ignore the experiences of individuals and society. The dual movement theory tries to align Islamic teachings with the needs of contemporary life. The double movement, as articulated by Fazlur Rahman, serves as an important structure for understanding the relationship between traditional texts and contemporary social challenges.